Phytochemical profiling and antioxidant potential of Pandanus leram (Pandanaceae) fruit pulp: A component crop of coconut ecosystem in Nicobar Islands, India - Jaisankar, I.; Ramesh, S.V.; Augustine Jerard, B.; Lakshmana Prabu, S.; Asokan, Hari Nivas; Blesy, G.M.; Arthi, N.; Umamaheswari, A.; Sanjeev, B. (Journal of Plantation Crops, 2025)
Pandanus leram (family Pandanaceae) is an important tree typically found in the tropical islands of Andaman and Nicobar. It is found as a component crop in the coconut groves. The fruits, fruitlets, seed and leaves of the tree are widely utilized as staple food or therapeutic applications by the local community. Nevertheless, biochemical composition of the fruit pulp is not known and hence this study was designed to determine the presence of various bioactive components, and to evaluate their antioxidant potential. Three distinct accessions of Pandanus leram were collected from the Nicobar Islands and the accessions were curated in ICAR-NBPGR under IC numbers: IC 0646202 (Galathea), IC 0646205 (Kinyuka), and IC 0646206 (Kamorta). Biochemical evaluation of the fruit pulp showed that IC 0646202 exhibited high carbohydrate and total fat whereas Accession 2 (IC 0646206) showed high crude fibre. Nevertheless, accession 3 (IC 0646205) displayed a relatively high content of protein (4.4±0.122 g/100g). Analysis of the antioxidant potential of the accessions revealed the accession IC0646206 exhibited highest hydroxyl radical scavenging activity compared to other two accessions. Further analysis involved phytochemical screening and gas chromatography–mass spectrometry (GC–MS) of methanolic extracts from the fruit pulp of these accessions.The results unveiled the presence of 34, 32, and 32 bioactive compounds in Accessions IC 0646202, IC 0646205, and IC 0646206, respectively.This comprehensive study sheds light on the biochemical composition and antioxidant capabilities of Pandanus leram, offering valuable insights into its potential applications in nutrition and health.